1962
DOI: 10.3181/00379727-109-27284
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Protection Against the Diabetogenic Effect of Alloxan by Glucose.

Abstract: Although alloxan is widely used to produce experimental diabetes, the mechanisms of its toxic action on the beta-cells are not known. A promising approach to study this mechanism is the use of protective agents in vivo. A biochemically heterogenous group of compounds was found to protect the rat against the diabetogenic effect of alloxan ( 1,2). However, many of these substances did not prove very valuable since they seem to protect by a nonspecific adrenergic type of mechanism (3) , or by reacting nonenzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1967
1967
1988
1988

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The concurrent presence of a high concentration of either D-glucose, D-mannose, or 3-0-methyl-D-glucose with alloxan during this brief exposure interval provided almost complete protection of the B-cells from the inhibitory effect of alloxan on glucose-induced insulin release [17]. These same hexoses had been reported previously to block the diabetogenic action of alloxan in rats when administered prior to the injection of alloxan in vivo [1,4,15,22]. This in vitro perifusion system now makes it feasible to obtain quantitative information on the protective action of other agents against alloxan and to determine whether alloxan may prove to be a useful probe in studying the mechanism of induction of glucose-induced insulin release.…”
mentioning
confidence: 65%
“…The concurrent presence of a high concentration of either D-glucose, D-mannose, or 3-0-methyl-D-glucose with alloxan during this brief exposure interval provided almost complete protection of the B-cells from the inhibitory effect of alloxan on glucose-induced insulin release [17]. These same hexoses had been reported previously to block the diabetogenic action of alloxan in rats when administered prior to the injection of alloxan in vivo [1,4,15,22]. This in vitro perifusion system now makes it feasible to obtain quantitative information on the protective action of other agents against alloxan and to determine whether alloxan may prove to be a useful probe in studying the mechanism of induction of glucose-induced insulin release.…”
mentioning
confidence: 65%
“…It does not appear possible to explain these observations by an action of alloxan restricted to a putative membrane glucoreceptor. The possibility should be considered that alloxan enters B-cells [33,34] via the hexose carrier system where antagonists of glucose transport (3-0-methylglucose, cytochalasin B, phlorizin) exert their protective action [4,17,21,[34][35][36]. Alloxan would then interfere with cellular events crucial for the response to glucose and subsequently lead to a more general dysfunctioning of the releasing machinery.…”
Section: Mechanism Of Alloxan Actionmentioning
confidence: 99%
“…But the hexokinases, a group of glucose phosphorylating isoenzymes with high affinity for glucose, which are present in all cells of the organism, could not be the target for expression of the selective effects of alloxan on the pancreatic B cells. Some years later, Carter and Younathan reported that the non-metabolisable sugar 3-O-methylglucose also protected against the diabetogenic action of alloxan [40].…”
Section: Alloxan Diabetesmentioning
confidence: 99%